Derivation and internal validation of an equation for albumin-adjusted calcium at a tertiary hospital in Selangor, Malaysia - Azmi, Jannaltul Adni; Thambiah, Subashini C.; Abdul Hamid, Hanisah; Zahari Sham, Siti Yazmin; Samsudin, Intan Nureslyna; Osman, Malina (Fakulti Perubatan dan Sains Kesihatan Universiti Putra Malaysia, 2020)
Introduction: Total calcium concentration is widely used to assess body calcium status although limited by many confounding factors. Thus, this study aimed to derive and internally validate an albumin-adjusted calcium equation for a selected Malaysian population. Method: This cross-sectional study involved 1011 adults at an emergency department of a tertiary hospital. Patients who had total calcium, ionised calcium and albumin measurements taken simultaneously were included. Derivation of the albumin-adjusted calcium equation was based on the adjustment equation obtained from the Association for Clinical Biochemistry and Laboratory Medicine 2015 position paper. Additionally, the equation was internally validated and compared with ionised calcium (gold standard) and the conventional Payne’s equation. Results: The newly derived equation = total calcium + 0.017 (41.35 – albumin). Internal validation exhibited the amount of shrinkage of 0.049. It tends to overestimate the adjusted calcium by a mean difference of 0.029 mmol/L compared to Payne’s equation. The comparison between Payne’s equation and the new equation with ionised calcium reclassified 402 and 486 patients, respectively into different calcium status. When both equations were compared, calcium status classification significantly differed in all and hypoalbuminaemic subjects by 90 and 16 patients, respectively. Conclusion: Locally derived albumin-adjusted calcium equation differed statistically in calcium status classification when compared to the Payne’s equation. However, to confirm this significance, the result must be compared to ionised calcium under strict, controlled preanalytical conditions. In terms of clinical significance, there was no difference in classification of calcium status between Payne’s and the new equation at medical decision limits.